Miskonsepsi pada Materi Perkembangbiakan dan Pertumbuhan Makhluk Hidup pada Kelas XII - Ulfa, Syarifah Widya; Afrianti, Billah; Rambe, Diva Raya Kinanti; Khairuddin, Faritz; Handayani, Fitriya; Rifda, Rifda (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
What are students' misconceptions about understanding the growth and development of living things and why students have difficulty learning the material on the growth and development of living things. This research aims to describe the profile of students' misconceptions on the growth and development of living things and to describe the factors causing students' misconceptions on the growth and development of living things. This data is really needed to determine the level of students' understanding of the concepts in the material. This research is a descriptive research. This research is broadly divided into two stages, namely the preparation stage and the implementation stage. This research is a descriptive research. The object of this research is the Growth and Development of Living Creatures material in the SMA/MA Class Living Creatures in the SMA/MA Class Material like this contained in books can be a misconception for students because the title is unclear so that students misunderstand what the title means. This research shows that there are misconceptions in books used as teaching materials in class XII in Biology lessons, these misconceptions can be found in the title, subtitles and even in the content of the material in this book. This book is quite clear and structured in delivering biology material, especially Growth and Development material, to high school/MA class XII students.